Financial planning in exporting SMEs in Antioquia, Colombia (2019)
SMEs constitute an important basis for economic growth, entrepreneurial network creation and employment generation in any country. From the onset of the twenty-first century, several institutional policy amendments have been consolidated in Colombia to strengthen the SMEs sector and to integrate it to the export competitiveness and growth goals The objective of this research was to determine how exporting SMEs from Antioquia have structured proper planning and financial management processes that could provide solid basis for entrepreneurial growth. An empirical approach was applied to study 39 regional enterprises, the results allow concluding that the so analyzed enterprises are still characterized by their challenges in financial decision making related to investment, financing sources and profit distribution.